Intricate relations : sexual and economic desire in American fiction, 1789-1814 - Weyler, Karen A. (University of Iowa Press, 2004)
Intricate Relations charts the development of the novel in and beyond the early republic in relation to these two thematic and intricately connected centers: sexuality and economics. By reading fiction written by Americans between 1789 and 1814 alongside medical theory, political and economic tracts, and pedagogical literature of all kinds, Karen Weyler recreates and illuminates the larger, sometimes opaque, cultural context in which novels were written, published, and read. In 1799, the novelist Charles Brockden Brown used the evocative phrase "intricate relations" to describe the.